Peran Pengasuh Pesantren Hidayatut Thalibin dalam Membentuk Nilai Keagamaan Santri Melalui Kitab Fathul Qarib - Ifadatul Afifah; Najmi Faza (Medan Resource Center, 2023)
This article aims to examine the role of caregivers at Hidayatut Thalibin Islamic Boarding School in shaping students' religious values through the Book of Fathul Qarib. Education plays a crucial role in shaping individuals, as it forms the foundation of their overall personality. In Islam, religious and moral education holds great significance and is an integral part of human life. Without religion and morals, humans would resemble a collection of aimless creatures without order in their lives. This qualitative research adopts a descriptive approach, with data analysis involving data reduction, presentation, and drawing conclusions. Triangulation is employed to ensure data validity. The findings of this study reveal the following: 1. The formation of religious values through the Book of Fathul Qarib, accomplished through memorization and interactive question-and-answer sessions facilitated by caregivers. 2. Supporting factors include direct motivation from caregivers and effective teaching methods employed by them, while inhibiting factors encompass lack of concentration and restlessness among students.